Are Argonaute-Associated Tiny RNAs Junk, Inferior miRNAs, or a New Type of Functional RNAs? - Nakanishi, Kotaro (Frontiers in Molecular Biosciences, 2021)
The biosynthesis pathways of microRNAs (miRNAs) have been well characterized with the identification of the required components. miRNAs are synthesized from the transcripts of miRNA genes and other RNAs, such as introns, transfer RNAs, ribosomal RNAs, small nucleolar RNAs, and even viral miRNAs. These small RNAs are loaded into Argonaute (AGO) proteins and recruit the effector complexes to target mRNAs, repressing their gene expression post-transcriptionally. While mature miRNAs were defined as 19–23 nucleotides (nt), tiny RNAs (tyRNAs) shorter than 19 nt have been found to bind AGOs as equivalent or lesser miRNAs compared to their full-length mature miRNAs. In contrast, my recent study revealed that when human AGO3 loads 14 nt cleavage-inducing tyRNAs (cityRNAs), comprised of the first 14 nt of their corresponding mature miRNA, it can become a comparable slicer to AGO2. This observation raises the possibility that tyRNAs play distinct roles from their mature form. This minireview focuses on human AGO-associated tyRNAs shorter than 19 nt and discusses their possible biosynthesis pathways and physiological benefits, including how tyRNAs could avoid target-directed miRNA degradation accompanied by AGO polyubiquitination.